ESPE/LWPES consensus statement on diabetic ketoacidosis in children and adolescents. Issue 2 (21st January 2004) - Dunger, D B; Sperling, M A; Acerini, C L; Bohn, D J; Daneman, D; Danne, T P A; Glaser, N S; Hanas, R; Hintz, R L; Levitsky, L L; Savage, M O; Tasker, R C; et al.
Abstract : Diabetic ketoacidosis (DKA) is the leading cause of morbidity and mortality in children with type 1 diabetes mellitus (TIDM). Mortality is predominantly related to the occurrence of cerebral oedema; only a minority of deaths in DKA are attributed to other causes. Cerebral oedema occurs in about 0.3–1% of all episodes of DKA, and its aetiology, pathophysiology, and ideal method of treatment are poorly understood. There is debate as to whether physicians treating DKA can prevent or predict the occurrence of cerebral oedema, and the appropriate site(s) for children with DKA to be managed. There is agreement that prevention of DKA and reduction of its incidence should be a goal in managing children with diabetes.